Growth, expectations, and tariffs - Seppo Honkapohja; Arja H. Turunen-Red; Alan D. Woodland (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study a many country endogenous growth model in which decisions about innovation and new investment are influenced by growth expectations. Adaptive learning dynamics determine country-specific short run transition paths. Countries differ in basic structural parameters and may impose tariffs on imports of capital goods. Numerical experiments illustrate adjustment dynamics that follow the use of tariffs. We show that countries that limit trade in capital goods can experience dynamic gains both in growth and utility and that such gains persist the longer the larger the structural advantages of the region that applies tariffs. Substantial differences in the levels of innovation, consumption, output, and utility can appear, and asymmetries in economic outcomes that were present before trade restrictions are made more severe.
Keywords: F43; F15; 330; endogenous growth; expectations; learning; short run dynamics; tariffs; complementary capital goods; Neue Wachstumstheorie; Adaptive Erwartung; Investitionsgut; Zolltarif; Theorie